Comparison of Angiographic Outcomes of Side Branch Ostium at Bifurcation Coronary Lesion between Two-stent and One-stent Techniques - Seo, Jae-Bin; Park, Kyung Woo; Lee, Hae-Young; Kang, Hyun-Jae; Koo, Bon-Kwon; Kim, Sang-Hyun; Kim, Hyo-Soo (Journal of Korean medical science, 2015)
Although the favored strategy for coronary bifurcation intervention is stenting main vessel with provisional side branch (SB) stenting, we occasionally use two-stent strategy. The objective of this study was to investigate the angiographic outcome of SB ostium in two-stent group, compared with one-stent group. We analyzed 199 patients with bifurcation lesion who underwent percutaneous coronary intervention (PCI) with drug-eluting stent and follow up angiography. The patients were divided into one-stent group (167 lesions, 158 patients) and two-stent group (41 lesions, 41 patients). Prior to intervention, SB ostium minimal luminal diameter (MLD) was smaller in two-stent group than in one-stent group (1.08±0.55 mm vs. 1.39±0.60 mm; P=0.01). But, immediately after PCI, SB MLD of two-stent group became greater than that of one-stent group (2.41±0.40 mm vs. 1.18±0.68 mm; P<0.01). Six to nine months after PCI, this angiographic superiority in SB MLD of two-stent group persisted (1.56±0.71 mm vs. 1.13±0.53 mm; P<0.01), although there was larger late loss in two-stent group (0.85±0.74 mm vs. 0.05±0.57 mm; P<0.01). In terms of target lesion revascularization and target vessel revascularization rates, one-stent group showed better results than two-stent group. We could attain wider long term SB ostium after two-stent strategy than after one-stent strategy.